People with symptoms of depression and those at significant risk of suicide show differences in their personality profile and sense of meaning in life - Kacper Deska; Grzegorz Mirocha; Bartłomiej Bąk; Anna Mirgos-Wierzchowska; Marcin Kosmalski; Monika Różycka-Kosmalska; Tadeusz Pietras (Frontiers in Psychiatry)
IntroductionMedical students are exposed to various stressors. Among the many factors that determine the possibility of a mental crisis, there is also a personality profile and a sense of meaning in life.Materials and methodsSets of anonymous surveys were distributed among medical students of different years studying at the Medical University of Lodz. The set of surveys included a sociodemographic survey, Beck’s Depression Inventory version II (BDI-II), the NEO Five Factory Inventory (NEO-FFI), Reker’s Life Attitude Profile - Revised questionnaire (LAP-R), Osman’s Suicidal Behavior Questionnaire (SBQ-R).ResultsThe study cohort comprised of 276 students (mean age 21.7 years). According to the BDI-II, 79 participants (28.4%) were identified as having depressive symptoms. Additionally, 80 participants (28.9%) were assessed to be at significant risk of suicide according to the SBQ-R scale. Based on the results of these questionnaires, we identified four groups: 1. Participants with depressive symptoms (D). 2. Participants with suicide risk (SR), 3. Participants with both depressive symptoms with suicide risk (D and SR), 4. A control group. Students from D and D and SR groups, exhibited higher neuroticism scores compared to those with suicide risk alone (SR) and the control group. In terms of extroversion, the control and SR groups scored higher compared to the D with SR group. Participants with SR and those with D and SR had higher openness scores compared to the D and control groups. D and SR group obtained statistical lower score then control group in the terms of conscientiousness. In life control score, participants in D and D with SR group has significant lower score then SR and control group. The conditions: personal meaning index and life attitude balance in the control group achieved significantly higher values compared to all other groups.ConclusionPeople with depressive symptoms, suicide risk and both of these variables simultaneously differed in terms of personality profile and components influencing the meaning of life.